2022
DOI: 10.3390/jcm11040960
|View full text |Cite
|
Sign up to set email alerts
|

Severe Asthma, Telemedicine, and Self-Administered Therapy: Listening First to the Patient

Abstract: Severe asthma patients are at an increased risk of major complications and they need to be monitored regularly. The COVID-19 pandemic has notably impacted on the health care resources. The telemedicine approach applied to the follow-up of asthmatic patients has been proven to be effective in monitoring their disease and their adherence to the therapy. The aim of our study was to investigate the satisfaction of severe asthma patients before the activation of a telemedicine management, as well as their current e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Despite prescribers playing a major role in IgRT modality choice, the finding that the SCIg cohort was associated with a better perceived effectiveness compared with the IVIg cohort may be, in part, attributed to the SCIg cohort (especially the SCIg naïve cohort) feeling more empowered. Self-infusing SCIg users play a more active role in their treatment compared with their IVIg counterparts, giving them the feeling of empowerment [41][42][43][44]. Indeed, patient preference assessments highlight the importance of continually offering patients information and a choice of IgRT infusion options [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite prescribers playing a major role in IgRT modality choice, the finding that the SCIg cohort was associated with a better perceived effectiveness compared with the IVIg cohort may be, in part, attributed to the SCIg cohort (especially the SCIg naïve cohort) feeling more empowered. Self-infusing SCIg users play a more active role in their treatment compared with their IVIg counterparts, giving them the feeling of empowerment [41][42][43][44]. Indeed, patient preference assessments highlight the importance of continually offering patients information and a choice of IgRT infusion options [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…59 Severe asthma patients, including those on biologics, appear to be satisfied with carrying out home selfmeasurements, self-management, virtual consultations and self-administration of injectable treatments. 60 Telemedicine can even successfully improve patients' inhaler technique and adherence, through video-directly observed therapy. 61 Clearly, the time has come for an updated Cochrane review of telemedicine in asthma.…”
Section: Physician-instigated Healthcare Changes To Asthma Managementmentioning
confidence: 99%
“…Interestingly, a 2012 Cochrane review of 21 trials using telemedicine in asthma care found it did not impact on quality of life for those with mild asthma but prevented exacerbations and hospital admissions for those with severe asthma 59 . Severe asthma patients, including those on biologics, appear to be satisfied with carrying out home self‐measurements, self‐management, virtual consultations and self‐administration of injectable treatments 60 . Telemedicine can even successfully improve patients' inhaler technique and adherence, through video‐directly observed therapy 61 .…”
Section: Physician‐instigated Healthcare Changes To Asthma Managementmentioning
confidence: 99%
“…Moreover, strategies employing domiciliary administration of the drug by a nurse, if the patient cannot self-administer the medication were applied [70]. An Italian study about telehealth during COVID-19 showed a good adherence to biological therapies and a good satisfaction in telemonitoring in period in which face to face visits were discouraged [71].…”
Section: The Role Of Asthma Medicationsmentioning
confidence: 99%